BS EN 15634-5. Foodstuffs. Detection of food allergens by molecular biological methods. Part 5. Mustard (Sinapis alba) and soya (Glycine max). Qualitative detection of a specific DNA sequence in cooked sausages by real-time PCR (15th November 2021) - British Standards Institution
No abstract available